Development of Zirconia Substituted 1393 Bioactive Glass for Orthopaedic Application - YADAV, SANDEEP KUMAR; SARTHAK RAY; ERSHAD, MD.; VYAS, VIKASH KUMAR; PRASAD, SUNIL; AKHER ALI; SUSHMA YADAV; MANAS RANJAN MAJHI; RAM PYARE (Oriental Scientific Publishing Company, 2017)
Zirconia was used as a bone substitute, since it has excellent mechanical properties. It is also good bioinert to bone tissue. In this study, we report on zirconia substituted 1393 bioactive glass. In novel melt-derived “1393” Bioactive glass (53 SiO2 , 6Na2 O, 12 K2 O, 5MgO, 20CaO, and 4 P2 O5 wt %) with CaO was doped by ZrO2 for and were melted at 1400°C in alumina crucibles in electric furnace with air as furnace atmosphere. Bioactivity of these samples were analysed by put in the SBF for different time periods. Hydroxy Carbonate Apatite layer was developed and identiûed by FTIR, XRD and SEM. Chemical durability was also determined by weight loss method. Density of the samples were determined and found to increase significantly with increasing amount of (0-2 wt %) zirconia, reason is due to replacement of lighter element of CaO has been replaced by heavier element ZrO2. Finally, this investigation clearly concluded that ZrO2 substituted bioactive glass would be potential biomaterials for biomedical applications.
Keywords: Bio-active glasses, Simulated body fluid, XRD, SEM, FTIR, pH, Chemical durability, Density.